2018
DOI: 10.1128/aem.00354-18
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Nucleotide Insertion in a Drug Transporter Gene Induces a Thermotolerance Phenotype in Gluconobacter frateurii by Increasing the NADPH/NADP + Ratio via Metabolic Change

Abstract: Thermotolerant microorganisms are beneficial to the fermentation industry because they reduce the need for cooling and offer other operational advantages. Previously, we obtained a thermally adapted strain by experimental evolution. In the present study, we found only a single G insertion in the adapted strain, which causes a frameshift in a gene encoding a putative drug transporter. A mutant derivative strain with the single G insertion in the transporter gene (Wild-G) was constructed from the wild-type strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 73 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Such stress tolerance may be related to the generation of reactive oxygen species (ROS). Microbial cells generate a large amount of ROS, especially when grown at growth-limiting high temperatures ( Davidson et al, 1996 ; Matsushita et al, 2016 ; Chang et al, 2017 ; Nantapong et al, 2019 ), and thermally adapted strains have been shown to generate less ROS than the wild-type strain when grown at higher growth temperatures ( Matsumoto et al, 2018 , 2020 ). Acetic acid fermentation may similarly generate ROS due to structural damage to the cell membrane caused by acetic acid and/or ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such stress tolerance may be related to the generation of reactive oxygen species (ROS). Microbial cells generate a large amount of ROS, especially when grown at growth-limiting high temperatures ( Davidson et al, 1996 ; Matsushita et al, 2016 ; Chang et al, 2017 ; Nantapong et al, 2019 ), and thermally adapted strains have been shown to generate less ROS than the wild-type strain when grown at higher growth temperatures ( Matsumoto et al, 2018 , 2020 ). Acetic acid fermentation may similarly generate ROS due to structural damage to the cell membrane caused by acetic acid and/or ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental evolution is one of the means of obtaining thermotolerant microorganisms. Thermal adaptation has been previously achieved in various microorganisms, including Escherichia coli ( Rudolph et al, 2010 ; Rodriguez-Verdugo et al, 2014 ), Saccharomyces cerevisiae ( Caspeta et al, 2014 ), Acetobacter pasteurianus ( Azuma et al, 2009 ; Matsutani et al, 2013 ; Matsumoto et al, 2020 ), Komagataeibacter oboediens ( Taweecheep et al, 2019 ), and Gluconobacter frateurii ( Hattori et al, 2012 ; Matsumoto et al, 2018 ). Furthermore, the mechanism associated with thermotolerance was also analyzed using these strains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trehalose regulates the PPP in pathogenic fungi during infection [ 29 ]. Moreover, trehalose mediates thermotolerance in Gluconobacter frateurii ; research has shown that trehalose does not contribute to thermotolerance directly but that a metabolic change including increased carbon flux to the PPP is instead the key factor [ 30 ]. However, the studies above reflect the role of trehalose in a single metabolic pathway, and few reports have addressed the regulatory effects of trehalose in multiple metabolic pathways and in redirecting metabolic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Such stress tolerance may be related to the generation of reactive oxygen species (ROS). Microbial cells generate a large amount of ROS, especially when grown at growth-limiting high temperatures Matsushita et al, 2016;Chang et al, 2017;Nantapong et al, 2019), and thermally adapted strains have been shown to generate less ROS than the wild-type strain when grown at higher growth temperatures (Matsumoto et al, 2018.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Experimental evolution is one of the means of obtaining thermotolerant microorganisms. Thermal adaptation has been previously achieved in various microorganisms, including Escherichia coli (Rudolph et al, 2010;Rodriguez-Verdugo et al, 2014), Saccharomyces cerevisiae (Caspeta et al, 2014), Acetobacter pasteurianus (Azuma et al, 2009;Matsutani et al, 2013;, Komagataeibacter oboediens (Taweecheep et al, 2019), and Gluconobacter frateurii (Hattori et al, 2012;Matsumoto et al, 2018). Furthermore, the mechanism associated with thermotolerance was also analyzed using these strains.…”
Section: Introductionmentioning
confidence: 99%